THE EFFECT OF CONTROLLED PERMEABILITY FORMWORK WITH DIFFERENT CURING METHODS ON THE DURABILITY CHARACTERISTICS OF CONCRETE - Adam, Andi Arham (MEKTEK, 2010)
Controlled Permeability Formwork (CPF) can be used to improve the strength, durability and appearance ofconcrete. This is achieved by allowing excess water and gas to escape at the surface adjacent to theformwork. This paper reports a study aimed at assessing whether such permeable formwork can be used toreduce curing times whilst maintaining durability and strength characteristics. An experimental study isdescribed where trial walls are constructed and tested at various ages following different curing periods andregimes. Results are presented that compare the outcomes of using permeable membrane with those of usinga traditional formwork. Comparisons of durability characteristics are were. The durability of the walls wasassessed by techniques such as: permeability; and water absorption. Results are presented in terms of howdifferent curing regimes can be employed to achieve equivalent characteristics. A discussion of how suchtechniques may be used to reduce construction time is presented.